Guest

if 2(a-b) + x(b-c)^2 + (c-a)^3 = 2(a-d) + (b-d)^2 + (c-d)^3 then a) x>=16 b)-8 =16

if 2(a-b) + x(b-c)^2 + (c-a)^3 = 2(a-d) + (b-d)^2 + (c-d)^3 then


a) x>=16   b)-8<=x<=16    c)x<=-8   d)x<=-8 or x>=16

Grade:12

1 Answers

Viral A. Parmar
41 Points
10 years ago

i am going to tell you how to solve all this type of q.

Best method according to me is substiute answers in q.

first assume any values of a,b,c,d (because it is in jounral so u can assume any it would be correct only)

then try putting all possibilities of x given in answer which satisfy that would be your answer thats it.....

 

if u liked my answer plz aprove it bu clicking on yes thank u Laughing

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free